Treatment of Oil Well Drill Cuttings Utilizing Different Binder Options - Abdullah, Raad M.; Othman, Mohammed A.; Abdullah, Siraj M. (Science Journal of University of Zakho, 2022)
A lab-scale treatability experiment was conducted on oil well drill cuttings (waste generated during petroleum exploration) using two different binders (Portland Cement and Lime) as a Solidification and Stabilization S/S agent. Seven ratios for each binder to waste (Drill cuttings) have been separately prepared (0.25:10, 0.5:10, 1:10, 2:10, 3:10, 4:10, 5:10) in which effects for each ratio and curing time (90 days) have been investigated on pH, chloride, and leachate for heavy metals (Ba, Pb, Cd, Ag, and Cr) through Toxicity Characteristic Leaching Procedure (TCLP). Results presented that the leaching of heavy metals (Ba, Cd, Cr, and Ag) was under the US EPA TCLP limit for all ratios with both binders. However, the Pb for the ratios of 0.25:10, 0.5:10, 2:10, and 3:10 for the cement-treated drill cuttings and 0.25:10 and 0.5:10 for the lime-treated drill cuttings have exceeded the proposed limit by the US EPA TCLP limit. Chloride also failed to meet the Nigerian chloride limit for drill cutting with the ratios 0.25:10, 0.5:10, 1:10, and 2:10 for both binders; meanwhile, the chloride concentrations were under the same limit within the ratios 3:10, 4:10, and 5:10. The overall results indicated that the binder options had affected the S/S product. Furthermore, the ratios of 1:10 and 2:10 had better performance considering the weight of the binders used for both options. The ratios of 4:10 and 5:10 had also performed well, but due to the significant quantities of the binders used, these ratios will not be considered economically feasible. The present investigation demonstrated that both binders could be used and relied on as an S/S agent aiming at treating drill cuttings. TRANSLATE with x <input id="LanguageMenu_svid" style="display: none;" autocomplete="on" name="LanguageMenu_svid" type="text" value="en"> <input id="LanguageMenu_textid" style="display: none;" autocomplete="on" name="LanguageMenu_textid" type="text"> English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian TRANSLATE with COPY THE URL BELOW <input id="ShareTextbox" name="ShareTextbox" readonly="readonly" type="text"> <!–a id="TwitterLink" title="Share on Twitter"> <a– id="FacebookLink" title="Share on Facebook"> </a–> Back <input id="EmailSubject" name="EmailSubject" type="hidden" value="Check out this page in 0 translated from 1"> <input id="EmailBody" name="EmailBody" type="hidden" value="Translated: 0%0d%0aOriginal: 1%0d%0a%0d%0aAutomatic translation powered by Microsoft® Translator%0d%0ahttp://www.bing.com/translator?ref=MSTWidget"> <input id="ShareHelpText" type="hidden" value="This link allows visitors to launch this page and automatically translate it to 0."> EMBED THE SNIPPET BELOW IN YOUR SITE <input id="EmbedSnippetTextBox" name="EmbedSnippetTextBox" readonly="readonly" type="text" value=" "> Enable collaborative features and customize widget: Bing Webmaster Portal Back